“They won’t hear me scream here”: Violence and horror in recent Latin American narrative written by women - Gasparini, Sandra (2022)
A wide variety of contemporary Latin American female writers have chosen to narrate violence using gothic horror and its devices in recent years. These are not necessarily narratives that respond to the most stable forms of the terror or horror genre. These are fictions that uses their procedures to bring the monstrous to the fore, the reification of the female and dissident body, subordination and feminicide, in order to postulate that not only the “maintenance of patriarchy is a matter of State”, but which is also “preserving the lethal capacity of men and guaranteeing that the violence they commit remains unpunished” (Segato). In many of these fictions, it is not only a matter of discovering how monsters are built, but also of detecting them in different positions of power: as resistance or as sovereigns.Gothic, in this corpus, goes through terror and violence in its domestic, family forms, through sexual abuse, the persecution of sexual dissidence, child abuse, pedophilia. The demonic appears in patriarchal structures and disseminated in the brutal practices of rites, sects, gangs. The representation of social exclusion, in which the victims of this relentless implementation of neoliberalism are the protagonists, occupies the whole narrations, as well as the foregrounding of sexual taboos overshadowed by hypocritical morality and the denounce of ecocide. The narratives of Mariana Enríquez, Agustina Bazterrica, Dolores Reyes, Fernanda Melchor, Mónica Ojeda, María Fernanda Ampuero and Yeniva Fernández will be the main focus of this article.